Dampak Serta Strategi UMKM Saat Pandemi Covid-19 Di Kabupaten Sidoarjo - Indah Widyaningtyas; Farida Rahmawati (Ekonomi dan Bisnis, 2021)
Changes in consumer behavior and people's consumption patterns during the COVID19 pandemic have made bag and suitcase SMEs in Kedensari Village feel the social and economic impact. The changes that occur require MSMEs to make strategies to deal with unexpected problems. So the purpose of this study is to compare the socioeconomic impact of MSMEs before and during the COVID-19 pandemic and formulate strategies that can be applied by MSME bags and suitcases during the Covid19 pandemic. This study uses a descriptive qualitative approach. Methods of data collection using interviews, observation, and documentation. In analyzing the data using collection, reduction, display, and drawing conclusions. The results showed that the number of visitors, training, and sales results decreased and unemployment in Kedensari Village increased. The IE matrix shows the position of MSME bags and suitcases in cell 1 with an x-axis of 3.51 and a y-axis of 3.27. There are three strategies from the results of the SWOT matrix analysis that have the highest TAS based on calculations on the QSPM matrix, namely increasing promotions through online sales media, exploring other businesses during a pandemic, and conducting focus group discussions.